The Scope for MDB Leverage and Innovation in Climate Finance - Basu, Priya; Finneran, Lisa; Bishop, Veronique; Sundararaman, Trichur (World Bank, Washington, DC, 2017)
This note, prepared as background for the G20 submission, explores the potential for Multilateral Development Banks (MDBs) to increase the volume of climate financing by leveraging and intermediating resources, through two main avenues: leveraging shareholder capital through the MDBs non-concessional windows, by raising debt from capital markets to finance climate investment; and mobilizing and 'pooling' concessional flows to support climate investment beyond the MDBs own balance sheets. The note is organized along these two lines, with the aim of providing some insights into the feasibility for MDBs to mobilize resources to leverage a significantly larger volume of climate financing assistance. The next section of this note provides information on how MDBs can support concessional flows to climate investments through pooling of external concessional flows beyond traditional balance-sheet capital. Leveraging shareholder capital and mobilizing and-pooling concessional flows are two potential avenues through which MDBs can leverage and intermediate resources to ultimately increase the volume of climate financing. The experience gained by the MDBs and their clients and donors from implementing these financing arrangements should provide helpful lessons for the development community as it considers how to develop the green climate fund and other future climate change initiatives.